2013
DOI: 10.1088/0964-1726/23/2/025013
|View full text |Cite
|
Sign up to set email alerts
|

A traveling wave piezoelectric beam robot

Abstract: In this paper, the operation principles of a traveling wave piezoelectric beam robot are presented. A prototype consisting of an aluminum beam structure, with two non-collocated piezoelectric patches bonded on its surface, was fabricated and tested to demonstrate the generation of a traveling wave on the beam based on the one mode excitation and the two mode excitation operation principles for propulsion. A numerical model was developed and used to study and optimize the generated motion of the piezoelectric b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 14 publications
0
70
1
Order By: Relevance
“…Experiments have shown that it was possible to control phase and amplitude even in transient and obtained a large travelling wave with standing wave ratio nearly equal to one. The principal applications domain of travelling wave are acoustic levitation [9]- [11], piezoelectric miniature robot [12], [13], Transportation of objects using linear ultrasonic motor [14]- [18]. In the first part, the principle of a new excitation method of vibration modes, using multi-modal approach is presented, with analytical modelling, showing the possibility to excite the beam with vibration amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that it was possible to control phase and amplitude even in transient and obtained a large travelling wave with standing wave ratio nearly equal to one. The principal applications domain of travelling wave are acoustic levitation [9]- [11], piezoelectric miniature robot [12], [13], Transportation of objects using linear ultrasonic motor [14]- [18]. In the first part, the principle of a new excitation method of vibration modes, using multi-modal approach is presented, with analytical modelling, showing the possibility to excite the beam with vibration amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…We observe that the amplitude of the wave is determined by the initial condition V(0, 0). The traveling waves for elastoplastic beams can be applied to study piezoelectric robots; see [27].…”
Section: Traveling Waves In Rods and Beams Of Arbitrary Lengthmentioning
confidence: 99%
“…Let us consider the initial conditions ( , 0) = 1 ( ) and ( , 0) = 0. In this case we have (0) = 1 and we can solve the second equation in (27). A special solution of this initial value problem is given by…”
Section: Special Waves In Rods and Beams Of Finite Lengthmentioning
confidence: 99%
“…For those robots whose movement relies on the generation of stationary waves, millimeter-sized legged devices have already been reported [14][15][16]. Furthermore, in the case of traveling waves, the state of the art involves the locomotion of 180-mm long plates actuated by piezoelectric patches, without using legs [17,18]. Taking these as the background, the present work aimed to further develop the traveling-wave-based locomotion of miniature plates with two piezoelectric patches.…”
Section: Introductionmentioning
confidence: 99%